Circulating endometrial cells in peripheral blood - Bobek, Vladimir; Kolostova, Katarina; Kucera, Eduard (European journal of obstetrics, gynecology, and reproductive biology, 2014)
OBJECTIVES: Endometriosis is a common disorder amongst women of reproductive age. Despite extensive research, no reliable blood tests currently exist for the diagnosis of endometriosis STUDY DESIGN: We report several new approaches enabling study of cell specific characteristic of endometrial cells, introducing enrichment and culturing of viable circulating endometrial cells (CECs) isolated from peripheral blood (PB) and peritoneal endometrial cells (PECs) from peritoneal washing (PW). Size-based enrichment method (MetaCell(®), Czech Republic) has been used for the filtration of PB and PW in patients with diagnosed endometriosis. RESULTS: The PECs were found in the PW in all of the tested patients (n=17), but CECs) only in 23.5% (4/17) cases. Their endometrial origin has been proved by immunohistochemistry. PECs were successfully cultured in vitro directly on the separating membrane (9/17) exhibiting both endometrial cell phenotypes: stromal and glandular within the culture. CECs were successfully cultured in the two of the four positive cases, but in none of them confluence has been reached. The occurrence in CECs in PB is clear and very specific evidence of an active endometrial disease. CONCLUSIONS: We demonstrated efficient, quick and user friendly endometrial cells capture platform based on a cell size. Furthermore, we demonstrated an ability to culture the captured cells, a critical requirement for post-isolation cellular analysis directed to better understanding of endometriosis pathogenesis.
Keywords: dospělí; endometrióza; Female; MetaCell; Adult; ženské pohlaví; endometrium; Immunohistochemistry; Endometriosis; Cultivation; lidé; Ascitic Fluid; Circulating endometrial cells; kultivované buňky; imunohistochemie; separace buněk; Cells, Cultured; CEC; Biomarker; Endometrium; Peritoneal Lavage; Cell Separation; ascitická tekutina; peritoneální výplach; buněčné kultury; Cell Culture Techniques; Humans